The influence of process optimization on the fermentation profile of mango wine prepared from the Apple mango variety - Musyimi, S.M.; Sila, D.N.; Okoth, E.M.; Onyango, C.A.; Mathooko, Francis M. (My University, 2013)
The aim of this study was to determine the effects of temperature and yeast concentration on the fermentation kinetics and chemical properties of Apple mango fruit wine through process optimization. The physicochemical properties of Applemango variety were determined for its suitability to produce wine. The fermentation conditions were optimized by varying temperature at 20°C, 25°C, 30°C and 35°C and the yeast concentration at 0.0065%, 0.01%, 0.05% and 0.1%. The increase in temperature and yeast concentration increased the fermentation kinetics significantly (p<0.05). However, at high temperature (35°C) and yeast concentration (0.1%) the sugars were not completely utilized during fermentation. At low temperature of 25°C, the alcohol yield was highest (9.44%) relative to high temperature of 35°C that gave the lowest yield (6.93%). Yeast concentration of 0.05% and fermentation temperature of 25°C gave the optimal characteristics for Apple mango wine using wine yeast (Saccharomyces cerevisae).